Learning Event 9, Agriculture and Rural Development Day at Rio+20 (Part 1/2) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Learning Event 9, From field to fork to field: nutritious food and nutrient cycling to enhance health, wealth and resilience The 9th learning event at the ARDD showcased the value wise crop choices for more nutritious food as well as the value of nutrient cycling in crop production. Using case studies from Niger and the Philippines the 'case to scale' effect different parts of the loop were demonstrated. Chair: Thomas Rosswall, CCAFS Independent Science Panel Chair Rapporteur: Matthew Fielding, SIANI Programme Officer 5 mins Introduction to learning event and speakers, Chair, Madeleine Fogde, SIANI Programme Manager 15 mins Closing loops and opening minds, nutrients recycling in Aguié, Niger - Mahamane Adamou, Agronomist at PPILDA 15 mins Vegetable gardens a nexus for agriculture, nutrition and health, Dr Robert Holmer, AVRDC The World Vegetable Centre 10 mins Synthesis of cases Chair 25 mins Smaller group discussion (1 speaker per group -- 4 groups) 15 mins Summing up from group discussions 5 mins Post-Rio thoughts